A new cynodont concentration from the brazilian triassic: insights into the genesis and paleobiological significance of a highly productive fossil site - (:unkn) unknown (Universidade Federal do Pampa, 2024)
It is important to analyze bioestratinomic evidence to understand the taphonomic history and reconstruct paleoecology. Over the years, taphonomic research on Triassic fossil vertebrates from Rio Grande do Sul has been published, showing the diversity of fossil vertebrate concentrations. Among these, we report a new concentration of cynodonts at different ontogenetic stages belonging to the species Exaeretodon riograndensis from the Várzea do Agudo outcrop, Triassic of Rio Grande do Sul. As previously proposed in the literature, the hypothesis of biogenic factors, resulting in an accumulation of skeletal elements by predators, would be key to the origin of such concentrations. Our new integration of taxonomic and taphonomic data allowed us to conclude that several factors are involved in the formation of the bone beds at the outcrop. The dynamics of the sedimentary environment, along with the accessory action of other organisms, would be the potential formers of this assemblage. The discovery of the new E. riograndensis assemblage contributes to a better understanding of the paleoecology of the taxon, as well as the inference of probable gregarious behavior, and aids in understanding the peculiar abundance of fossil vertebrates at the Várzea do Agudo site.
Keywords: Tafonomia; Exaeretodon riograndensis; Leitos de ossos; Triássico; Paleoecologia; Taphonomy; Exaeretodon riograndensis; Bonebeds; Triassic; Paleoecology; CNPQ::CIENCIAS BIOLOGICAS